The Interplay of Relational and Non-relational Processes in Sentence Production: The Case of Relative Clause Planning in Japanese and Spanish - Rodrigo, Laura; Igoa, José M.; Sakai, Hiromu (Frontiers in Psychology, 2018)
Speech planning involves different steps in order to transform a conceptual message into speech. These include establishing structural relations among constituents (i.e., relational information), and selecting the appropriate lexical items to convey the intended message (non-relational elements). However, the precise way relational and non-relational information are computed when undertaking linguistic encoding is not clear. This paper explores how the pre-linguistic message undergoes linguistic encoding, and what kind of information (relational or non-relational) is prioritized in doing so. We analyze the production planning of Relative Clauses in Spanish (a head-initial language) and Japanese (a head-final language) by monolingual speakers, by means of the eye-tracking method while participants described colored pictures. Although in both Spanish and Japanese the structure under study is the same (with the same structural scaffold), word order is entirely opposite between both languages. In Japanese, the head noun is not uttered until the end of the clause, thus making it possible to explore sentence planning in a structure where the syntactic most dominant element (the head noun) is not the first element. Variables tested were type of relative clause, with either the agent or the patient as head noun, and the animacy of the agent and the patient of the event, the latter allowing to manipulate the conceptual saliency of the elements involved. Results showed Japanese speakers focus extensively on the HN before directing their gazes to the element they are going to utter first, suggesting a speech planning process that prioritizes relational information, that is, structural scaffolding. Spanish monolinguals, in turn, showed a pattern in which both structural and linear information appear to be more closely related from the beginning. In both languages, the animacy of isolated elements had little effect on gaze patterns. Results point to a planning process that prioritizes structural relations over access to lexical elements in order in the planning of complex structures, with room for flexibility when the grammar of the language allows so.